2019
DOI: 10.1101/694216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The P300 as marker of inhibitory control – fact or fiction?

Abstract: Inhibitory control, i.e., the ability to stop or suppress actions, thoughts, or memories, represents a prevalent and popular concept in basic and clinical neuroscience as well as psychology. At the same time, it is notoriously difficult to study as successful inhibition is characterized by the absence of a continuously quantifiable direct behavioral marker. It has been suggested that the P3 latency, and here especially its onset latency, may serve as neurophysiological marker of inhibitory control as it correl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…While, one interpretation of this partial EMG activity is that it merely reflects 'weak' Go activation that did not run to completion (De Jong et al, 1990), several lines of evidence strongly suggest it is a muscle manifestation of the stopped response. First, CancelTime was positively correlated with SSRT Beh , similar to recent studies (Huster et al, 2019;Thunberg et al, 2019). Second, the variability of CancelTime was positively correlated with the variability of SSRT estimated from the BEESTS modeling framework.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While, one interpretation of this partial EMG activity is that it merely reflects 'weak' Go activation that did not run to completion (De Jong et al, 1990), several lines of evidence strongly suggest it is a muscle manifestation of the stopped response. First, CancelTime was positively correlated with SSRT Beh , similar to recent studies (Huster et al, 2019;Thunberg et al, 2019). Second, the variability of CancelTime was positively correlated with the variability of SSRT estimated from the BEESTS modeling framework.…”
Section: Discussionsupporting
confidence: 85%
“…Frontal Eye Field decrease activity in less than 10 ms before SSRT (Hanes et al, 1998), dopaminergic neurons in rodent substantia nigra and striatum increase activity only 12 ms before SSRT (Ogasawara et al, 2018), TMS at ~25 ms before SSRT over human Intraparietal Sulcus prolongs SSRT (Osada et al, 2019), and P300 human EEG activity ~300 ms after the Stop signal relates to the stopping latency (Wessel and Aron, 2015). Whereas the rather late timing of some of these results might be related to processes such as monitoring and feedback (Huster et al, 2019) as has been ascribed to brain signatures that modulate after SSRT (Logan et al, 2015;Schall and Boucher, 2007), our earlier latencies for prefrontal bursts, TMS-MEP and muscle…”
Section: Discussionmentioning
confidence: 94%
“…While this corresponds to a large effect, it leaves much unexplained variance that could be driven by factors unique to each measure. Therefore, it seems reasonable to question the extent to which these markers should be used interchangeably as measures of inhibitory timing, a notion which is supported by recent work 48,49 . In sum, though, the correlational pattern suggests that while the different proposed stopping latency markers are not necessarily overlapping in time ( Figure 2), they are indeed related to each other as well as to general task processing as quantified by the go reaction times.…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected from 37 participants (20 females, 17 males) between the age of 19 and 35 years (average age 26.8). The SST data is also used in Huster et al (2019). All participants were righthanded, reported no psychiatric or neurological disorders and had normal or corrected-to-normal vision.…”
Section: Samplementioning
confidence: 99%
“…Further, Wessel (2017) manipulated the task parameters of the GNGT and found that the stop-related P3 was elicited in the GNGT only if the probability of no-go stimuli was low and the task pace was fast enough to evoke a prepotent response tendency. However, others have argued that the P3 appears too late to index a genuine inhibitory process (Filipović et al, 2000;Huster et al, 2019;Raud and Huster, 2017;Skippen et al, 2019). While the P3 onset is typically detected at around 200-300 ms, corticomotor excitability is reduced already at around 150 ms inhibitory signal onset (Coxon et al, 2006;Fujiyama et al, 2011;Hoshiyama et al, 1997Hoshiyama et al, , 1996Macdonald et al, 2014;van Campen et al, 2013;van den Wildenberg et al, 2010;Yamanaka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%